COMIENDOP: a protocol to improve the motivational teaching styles of pre-service primary physical education teachers - Sanz-Remacha, María; Julián-Clemente, José Antonio; Aibar, Alberto (Frontiers in Education, 2025)
IntroductionPre-service primary teachers, especially primary Physical Education (PE) teachers, must acquire core teaching skills and effective classroom management strategies. The acquisition of motivating teaching styles in PE lessons has positive consequences for both teachers and students. Grounded in Self-Determination Theory and the Circumplex Model, the present study presents the first intervention program designed to foster motivating teaching styles (i.e., autonomy support and structure) and prevent (de)motivating teaching styles (i.e., control and chaos) among preservice primary PE teachers.MethodsThe training program also strives to improve preservice primary PE teachers’ competence and motivation, which might increase motivation for PE and physical activity engagement in the students later under their charge. A quasi-experimental design was employed that took a mixedmethods approach. A total of 370 participants from the [anonymized peer review process] will participate in the study. Participants were divided into control and experimental groups. The intervention program is structured into two main phases (i.e., general and specific phases) and will last a total of 35 h. Theoretical and practical face-to-face sessions will be conducted by university PE specialist professors. Following the training program, participants will complete school placements to apply what they have learned.Findings and discussionPre-service primary PE teachers will learn to effectively use motivational strategies and teaching skills, whilst also adopting motivating teaching styles during practical sessions. Motivation, (de)motivating teaching styles, and perceptions of efficacy and competence will be assessed via questionnaires and focus groups. Findings represent an important first step towards improving motivational training programs for pre-service primary PE teachers and improving the quality of university teaching.